MODERN POSSIBILITIES IN THE DIAGNOSIS OF PERITONITIS - Maqsudova Anisa; Nurmatova M.A. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Peritonitis is one of the most serious and life-threatening conditions in abdominal surgery and clinical medicine. This disease is characterised by inflammation of the peritoneum, accompanied by a pronounced systemic inflammatory response, rapid progression and a high risk of developing multiple organ failure. Despite the significant achievements of modern medicine, the mortality rate for peritonitis remains high and, according to various authors, ranges from 10 to 40%, and in widespread and postoperative forms can exceed 50% [1,2]. The relevance of the problem of peritonitis is due not only to the severity of the clinical course, but also to the variety of its aetiological factors. Peritonitis can develop as a complication of acute surgical diseases of the abdominal organs (appendicitis, perforation of gastric and duodenal ulcers, intestinal obstruction), trauma, postoperative complications, as well as infectious processes, including peritonitis associated with peritoneal dialysis. The variety of causes and clinical forms of the disease significantly complicates timely diagnosis [3,4]. One of the key problems in the management of patients with peritonitis remains early diagnosis, as the clinical manifestations of the disease in the early stages may be blurred or nonspecific. In some cases, the symptoms of peritonitis are masked by other acute abdominal conditions, leading to diagnostic errors and delays in the initiation of adequate treatment. It is known that every hour of delayed diagnosis directly worsens the prognosis of the disease and increases the risk of death [7,8].